2012
DOI: 10.5606/tgkdc.dergisi.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor SUVmax/lymph node SUVmax ratio viewed on PET-CT in the detection of mediastinal metastasis in patients with lung cancer

Abstract: Amaç: Bu çalışmada, küçük hücreli dışı akciğer kanseri (KHDAK) hastalarında mediastinal lenf nodu evrelemesinde pozitron emisyon tomografi-bilgisayarlı tomografinin (PET-BT) duyarlığını saptamada lenf nodu standardize alım değeri (SUDmax)/kitle SUDmax oranı araştırıldı.Ça lış m a pla nı: Çalışmamıza Ocak 2007 -Ekim 2010 tarihleri arasında Süreyyapaşa Göğüs Hastalıkları ve Göğüs Cerrahisi Eğitim ve Araştırma Hastanesi 9. Göğüs Hastalıkları kliniğinde patolojik olarak kanıtlanmış 31 KHDAK hastası (3 kadın, 28 er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although SUV max has no definitive diagnostic value, it has been reported that the SUV max value above 2.5-3 in mediastinal lesions strengthens the likelihood of malignancy. [20] When a SUV max cut-off value of 3 was used in the present study, the sensitivity, specificity, and accuracy of PET/CT in detecting malignancy were 93.5%, 46.1%, and 71.9%, respectively. Furthermore, the SUV max , SUV mean , MTV and HU values were found to be significantly higher in the malignant group than in the benign group in our study, and the optimal cut-off values for SUV max and SUV mean were 4.6 and 3.1, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…Although SUV max has no definitive diagnostic value, it has been reported that the SUV max value above 2.5-3 in mediastinal lesions strengthens the likelihood of malignancy. [20] When a SUV max cut-off value of 3 was used in the present study, the sensitivity, specificity, and accuracy of PET/CT in detecting malignancy were 93.5%, 46.1%, and 71.9%, respectively. Furthermore, the SUV max , SUV mean , MTV and HU values were found to be significantly higher in the malignant group than in the benign group in our study, and the optimal cut-off values for SUV max and SUV mean were 4.6 and 3.1, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…Data were reconstructed into coronal, sagittal, and transverse sections and a threedimensional rotating projection. SUV-max 2.5 and above for mediastinal lymph nodes were accepted as the cut-off value for malignancy (10).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were instructed to fast for six hours before the imaging, and FDG (370 MBq) was administered intravenously. Data were reconstructed into coronal, sagittal, and transverse sections and a three-dimensional rotating projection (11). A comparison was made between the mediastinal lymph node evaluation performed with PET in the preoperative period and the evaluation considered as the gold standard with the postoperative pathology.…”
Section: Pet-ct Imaging Protocolmentioning
confidence: 99%